An Investigation of Teachers’s Role as Facilitators in Teaching Writing in the Classroom - Purnama, Novi Dewi (Universitas Swadaya Gunung Jati, 2015)
The aim of this research is to describe in the teacher’s role as facilitator in teaching writing in the classroom. This research is qualitative approach by analysis teacher’s role as facilitator thought the data that have been collected from the student’s and the teacher’s. the technique of collecting data that used by the writer are observation in teacher’s role as facilitator, observation sheet, interview, video recording, and the result of observation. To know the kinds of teacher role as facilitator did teaching writing in the classroom. And the writer analysis teacher’s role in teaching writing in classroom by observation sheet giving mark on it and writer the correct it, until gets the result did. Then, the writer takes the conclusion of teacher’s role as facilitator and teacher interview to appropriate the teacher role in teaching writing in the classroom. This research find come that all of teacher role. Based on the result from interview the lecturer, the teacher as facilitator was applied the teacher.